Prevalence of potentially inappropriate medication among older patients in a primary care unit of a tertiary care hospital in Thailand: a retrospective cross-sectional study - Thareerat Ananchaisarp; Panya Chamroonkiadtikun; Kittipon Kodchakrai; Tanaboon Saeung; Thitiwut Charatcharungkiat; Patnaree Leelarujijaroen; Nopason Sae-Tang; Nanapat Kumkiem; Wipada Kanhin; Haran Sintateeyakorn; Kasidintorn Watcharajiranich (BMJ Open)
Objective Older adults are prone to developing multiple chronic diseases and have increased medication usage. This has led to the prescription of potentially inappropriate medications (PIMs). This study aimed to assess PIM prevalence among patients visiting the primary care unit (PCU) of a tertiary care hospital and evaluate the associated factors.Design A retrospective cross-sectional study by reviewing medical records in the hospital information system.Setting The PCU of a tertiary care hospital.Participants Patients aged ≥65 years who visited the PCU between 1 June and 30 November 2023 and received at least one oral medication.Primary and secondary outcome measures PIMs were diagnosed using the updated American Geriatrics Society Beers criteria 2023, and logistic regression was used to identify factors associated with PIM prescriptions.Results The study included 1600 participants, of whom 62.9% were female, with a median age of 72.0 years (IQR=68.0–77.0). The prevalence of PIMs was 39.4%. The three most common PIMs prescribed were diuretics, benzodiazepines and sulfonylureas. An increasing number of underlying diseases, presenting with acute illness (compared with follow-up only) and being treated by staff physicians (compared with trainee physicians) were significantly associated with increased odds of PIM prescriptions (adjusted OR (95% CI) = 1.59 (1.42 to 1.79), 1.58 (1.28 to 1.94) and 1.84 (1.33 to 2.54), respectively).Conclusion PIM prescriptions among older patients in the PCU were high, particularly in those with multiple comorbidities and acute illness presentations. Therefore, physicians should prescribe medications with caution, and various explicit criteria can be used as screening tools to prevent PIM prescriptions.